Optimal fiscal policy of a monetary union member - Seppo Orjasniemi (Bank of Finland, 2014)
In this essay we study the optimal noncoordinated fiscal policy in a monetary union, where a common and independent monetary authority commits to optimally set the union-wide nominal interest rate. The national governments in the monetary union implement independent fiscal policies by choosing the level of government expenditures. We show that under a non-coordinated optimal fiscal policy rule government spending should react counter cyclically to the local output gap and inflation, while the union-wide aggregate fluctuations are stabilized by the common monetary policy. We also show that the spillovers caused by asymmetric shocks depend on the relative size of the country subject to these shocks.
URN:NBN:fi:bof-201410313101
Keywords: E52; E62; F41; 330; monetary union; monetary policy; fiscal policy